Evaluation of Selected CYP51A1 Polymorphisms in View of Interactions with Substrate and Redox Partner - Režen, Tadeja; Ogris, Iza; Sever, Marko; Merzel, Franci; Golic Grdadolnik, Simona; Rozman, Damjana (Frontiers in Pharmacology, 2017)
Cholesterol is essential for development, growth and maintenance of organisms. Mutations in cholesterol biosynthetic genes are embryonic lethal and few polymorphisms have been so far associated with pathologies in humans. Previous analyses show that lanosterol 14α-demethylase (CYP51A1) from the late part of cholesterol biosynthesis has only a few missense mutations with low minor allele frequencies and low association with pathologies in humans. The aim of this study is to evaluate the role of amino acid changes in the natural missense mutations of the hCYP51A1 protein. We searched SNP databases for existing polymorphisms of CYP51A1 and evaluated their effect on protein function. We found rare variants causing detrimental missense mutations of CYP51A1. Some missense variants were also associated with a phenotype in humans. Two missense variants have been prepared for testing enzymatic activity in vitro but failed to produce a P450 spectrum. We performed molecular modelling of three selected missense variants to evaluate the effect of the amino acid substitution on potential interaction with its substrate and the obligatory redox partner POR. We show that two of the variants, R277L and especially D152G, have possibly lower binding potential towards obligatory redox partner POR. D152G and R431H have also potentially lower affinity towards the substrate lanosterol. We evaluated the potential effect of damaging variants also using data from other in vitro CYP51A1 mutants. In conclusion, we propose to include damaging CYP51A1 variants into personalized diagnostics to improve genetic counselling for certain rare disease phenotypes.